PSNP and sustainable land management in Ethiopia: A formative qualitative investigation - Tefera, Mulugeta; Gilligan, Daniel O.; Leight, Jessica; Tambet, Heleene (International Food Policy Research Institute, 2024)
The Productive Safety Net Program (PSNP) is Ethiopia’s national safety net program, launched in 2005 and currently in its fifth phase. The objective of the PSNP is to protect households’ food consumption and assets, reduce their vulnerability to shocks, and address underlying causes of extreme poverty (MoA FSCD 2020). Households who have an adult available to work are required to take part in public works that focus on building infrastructure and improving the natural resource base (MoA FSCD 2020). As such, these projects are partially designed to contribute to disaster risk reduction and climate change adaptation and mitigation. However, there is limited evidence about how sustainable land management (SLM) activities are conducted under the PSNP on both publicly and privately operated lands, and how the uptake of these activities and their benefits differ by gender.